<em>Answer:</em>
The inequality that is true is -5 - 3x > 10.
<em>Step-by-step explanation:</em>
if x = -6
we can subtitution x to every inequality, so :
-5 - 3x > 10
-5 - 3(-6) > 10
-5 - (-18) > 10
-5 + 18 > 10
13 > 10 [true]
-3 - 5x < -14
-3 - 5(-6) < -14
-3 - (-30) < -14
-3 + 30 < -14
27 < -14 [false]
2 - x < -3
2 - (-6) < -3
2 + 6 < -3
8 < -3 [false]
So if x=-6, inequality true is -5 - 3x > 10.
<em>If this was helpful, please mark brainliest. Have a beautiful day. </em>
<h2>(1)</h2><h2> =(a+b)(3c-d)</h2><h2> =a(3c-d)+b(3c-d)</h2><h2> =3ac-ad+3bc-bd</h2>
<h2>(2)</h2><h2> =(a-b)(c+2d)</h2><h2> =a(c+2d)-b(c+2d)</h2><h2> =ac+2ad-bc-2bd</h2>
<h2>(3)</h2><h2> =(a-b)(c-2d)</h2><h2> =a(c-2d)-b(c-2d)</h2><h2> =ac-2ad-bc+2bd</h2>
<h2>(4)</h2><h2> =(2a+b)(c-3d)</h2><h2> =2a(c-3d)+b(c-3d)</h2><h2> =2ac-6ad+bc-3bd</h2>
Answer:
The answer to your question is Long = 10.39
Step-by-step explanation:
Data
hypotenuse = 12
long = ?
Process
1.- To find Long, we must use the trigonometric functions sine or cosine.
If we use sine, we use the 60° angle
If we use cosine, we use the 30° angle
a) sin 60 = long / hypotenuse
Long = hypotenuse x sin 60
Long = 12 x sin 60
Long = 10.39
b) cos 30 = Long / hypotenuse
Long = hypotenuse x cos 30
Long = 12 x cos 30
Long = 10.39
Step-by-step explanation:
Hey there!
Given;
-6(2x-9) + (7-6x) = 0
Simplify it.
-12x + 54 + 7 - 6x = 0
-18x +61 = 0
Therefore, answer is option B.
<u>Hope</u><u> it</u><u> helps</u><u>!</u>